1999
DOI: 10.1177/107110079902000407
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of the Modified Brostrom-Evans Procedure to Restore Ankle Stability

Abstract: The modified Brostrom procedure has become the standard for anatomic repair of symptomatic chronic lateral instability. However, it was our perception that this local tissue repair may fail eventually, particularly in patients that are overweight, hyperflexible, or are involved in strenuous work or athletic activity. This is a retrospective review of 21 lateral ankle reconstructions (20 patients) in which the modified Brostrom technique was augmented with a portion of the peroneus brevis tendon. All patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
71
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(73 citation statements)
references
References 8 publications
(15 reference statements)
0
71
0
2
Order By: Relevance
“…There are a relatively large number of patients for whom the MBG is associated with a poorer outcome. This includes patients with generalized ligamentous laxity or joint hypermobility, long‐standing lateral ligament instability and failed previous surgery, as well as patients with adverse hindfoot biomechanics and high‐demand athletes …”
Section: Discussionmentioning
confidence: 99%
“…There are a relatively large number of patients for whom the MBG is associated with a poorer outcome. This includes patients with generalized ligamentous laxity or joint hypermobility, long‐standing lateral ligament instability and failed previous surgery, as well as patients with adverse hindfoot biomechanics and high‐demand athletes …”
Section: Discussionmentioning
confidence: 99%
“…For example, Evans 54 described in 1953 a transposition of the peroneus brevis tendon through a Shawen et al bone tunnel in the distal fibula followed by reattachment of the tendon to its remaining distal portion. Today this procedure is more commonly done, as described by Girard and colleagues, 55 using an anterior slip of the peroneus brevis as a checkrein, therefore avoiding complete disruption of the tendon and preserving most tendon function (Fig. 2).…”
Section: Surgical Treatmentmentioning
confidence: 98%
“…Girard et al thought that the modified Brostrom would eventually fail in patients who were overweight or hyperflexible or engaged in strenuous work or athletic activities in the long run. 11 Barbari et al found cases in which lateral ligamentous structures were insufficient, making a repair impossible and reconstructed procedure necessary. 12 Watson-Jones and Chrisman-Snook procedures are the most frequently used techniques for correcting chronic lateral ankle instability in reconstructed procedures, and Watson-Jones tendonsis has been regarded as a better method compared with other techniques.…”
Section: Discussionmentioning
confidence: 99%